The Relationship Between Heart Rate Variability and Electroencephalography Functional Connectivity Variability Is Associated With Cognitive Flexibility - Alba, Guzmán; Vila, Jaime; Rey, Beatriz; Montoya, Pedro; Muñoz, Miguel Ángel (Frontiers in Human Neuroscience, 2019)
The neurovisceral integration model proposes a neuronal network that is related to heart rate activity and cognitive performance. The aim of this study was to determine whether heart rate variability (HRV) and variability in electroencephalographic (EEG) functional connectivity in the resting state are related to cognitive flexibility. Thirty-eight right-handed students performed the CAMBIOS test, and their heart and EEG activity was recorded during 6 minutes in the resting state with their eyes open. We calculated correlations and partial correlations between HRV indices, functional brain connectivity variability and CAMBIOS scores. Furthermore, the sample was divided into groups according to CAMBIOS performance, and a one-way ANOVA was applied to evaluate group differences. Our results show direct correlations among cognitive flexibility and neuronal and heartbeat variability. Partial correlations suggest that the relation between HRV and CAMBIOS performance is mediated by neuronal oscillations. ANOVA analysis confirms that HRV and variability in functional brain connectivity predicted cognitive performance. In conclusion, the levels of brain signal variability could predict cognitive flexibility in a cognitive task, while HRV could predict cognitive flexibility only when it was mediated by neuronal oscillations.